Strategi Pembelajaran Fiqih Berbasis Kompetensi 4C (Communication, Collaboration, Critical Thinking and Problem Solving, dan Creative and Innovative) di MA Hasyim Asy’ari Jogoroto Jombang - Safitri, Silvia Sanabella; Anshori, Sholihul (Al Tadib : Jurnal Ilmu Pendidikan, 2024)
This journal discusses the 4C Competency-based fiqh learning strategies at MA Hasyim Asy'ari Jogoroto Jombang used by various teachers. In this case the learning strategy used in learning Fiqh is based on the 4C competencies, including: communication, collaboration, critical thinking and problem solving, and creative and innovative. Fiqh teachers carry out an innovation in learning, the innovation is in the form of using interesting learning strategies. With the teacher carrying out an innovation in learning strategies it can make it easy for students to understand the lessons given, and learning objectives can be achieved. Supporting factors for the 4C competency-based fiqh learning strategy at MA Hasyim Asy'ari Jogoroto Jombang are the active participation of the madrasa head, teachers, enthusiastic students, psychological and academic approaches, cooperative learning partners. The inhibiting factors include, student abilities, teacher age, competence that is still new, lack of motivation from related parties, student activity.